2007
DOI: 10.1159/000101410
|View full text |Cite
|
Sign up to set email alerts
|

IL-9 Production by Peripheral Blood Mononuclear Cells of Atopic Asthmatics

Abstract: Background: IL-9 might play a critical role in pathogenesis and development of atopic asthma, but there are few reports on allergen-specific IL-9 production by peripheral blood mononuclear cells (PBMCs) obtained from adult asthmatics. Methods: PBMCs were obtained from adult atopic asthmatics and incubated with Dermatophagoides farinae(Der f) extract for the designated time periods. The resulting supernatants were assayed for IL-9 by specific sandwich ELISA. Results: IL-9 production was detectable on day 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…High level of IL-9 production can be detected from the presensitized cells isolated from the peripheral blood of atopic infants when challenged with house dust mite or cat allergen in vitro [89]. Similar response can be detected in peripheral blood mononuclear cells (PBMCs), which are obtained from adult atopic asthmatics and incubated with Dermatophagoides farina (Der f) extract [78].…”
Section: Antigen-specific Th9 Cellmentioning
confidence: 92%
See 4 more Smart Citations
“…High level of IL-9 production can be detected from the presensitized cells isolated from the peripheral blood of atopic infants when challenged with house dust mite or cat allergen in vitro [89]. Similar response can be detected in peripheral blood mononuclear cells (PBMCs), which are obtained from adult atopic asthmatics and incubated with Dermatophagoides farina (Der f) extract [78].…”
Section: Antigen-specific Th9 Cellmentioning
confidence: 92%
“…It is reported that TGF-β reprograms Th2 cells to lose their characteristic profile and switch to IL-9-secreting cells [82]. Meanwhile, it is of great note that, unlike the observation in vitro, a considerable portion of Th9 cells acquire Th1 cell phenotype and produce Th1 type cytokine, IFN-γ in vivo [76,78]. This phenomenon may be due to multiple environmental signals including the local cytokine milieu in disease models and organs, shaping Th9 cell phenotype to improve and facilitate local adaptive immunity.…”
Section: The Plasticity and Stability Of Th9 Cellsmentioning
confidence: 99%
See 3 more Smart Citations